Priorities of Chemistry for a Sustainable Development-Priochem 2019
DOI: 10.3390/proceedings2019029095
|View full text |Cite
|
Sign up to set email alerts
|

Plant Biostimulants Based on Selenium Nanoparticles Biosynthesized by Trichoderma Strains

Abstract: Biostimulants are a novel class of additives used to promote plant vigor and resistance to abiotic stress, such as desiccation. The most used biostimulants are humic and fulvic acids, seaweed extracts, and biopolymers, as well as beneficial bacterial and fungal strains [1]. One such beneficial fungal strain is Trichoderma, which exists in the soil and colonizes the root system and can enhance root proliferation [2]. Trichoderma spp. were shown to be able to bio-synthesize selenium nanoparticles (SeNPs) [3]. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Harnessing SeNPs as Se-nanofertilizers holds the potential for synchronized Se management in terms of release and uptake by crops, while preventing Se losses in agroecosystems that may occur when commercial Se fertilizers containing selenate and selenite salts are employed (Babajani et al 2019). SeNPs seem to be less toxic to plants than selenate and selenite salts, as reported in tobacco (Nicotiana tabacum L.) (Domokos-Szabolcsy et al 2012), garlic (Allium sativum L.) (Li et al 2020) and Vigna radiata plants (Bărbieru et al 2019). They can also improve the quality traits of vegetables, as described in strawberry (Fragaria × ananassa) and tomato (Solanum Lycopersicon L.), whose fruits were more enriched in organic acids (e.g., malic, citric and succinic acids) and sugars (e.g.…”
Section: Biofortification By Using Nano-sized Seleniummentioning
confidence: 93%
“…Harnessing SeNPs as Se-nanofertilizers holds the potential for synchronized Se management in terms of release and uptake by crops, while preventing Se losses in agroecosystems that may occur when commercial Se fertilizers containing selenate and selenite salts are employed (Babajani et al 2019). SeNPs seem to be less toxic to plants than selenate and selenite salts, as reported in tobacco (Nicotiana tabacum L.) (Domokos-Szabolcsy et al 2012), garlic (Allium sativum L.) (Li et al 2020) and Vigna radiata plants (Bărbieru et al 2019). They can also improve the quality traits of vegetables, as described in strawberry (Fragaria × ananassa) and tomato (Solanum Lycopersicon L.), whose fruits were more enriched in organic acids (e.g., malic, citric and succinic acids) and sugars (e.g.…”
Section: Biofortification By Using Nano-sized Seleniummentioning
confidence: 93%
“…Organic plant biostimulants are seaweed and botanical extracts [ 106 , 107 , 108 , 109 ], humic and fulvic acids [ 110 , 111 ], protein hydrolysates [ 112 , 113 ], chitosan [ 114 , 115 ], and other biopolymers [ 116 , 117 , 118 ]. Inorganic plant biostimulants are plant-beneficial elements, such as silicon [ 119 , 120 ] or selenium [ 121 , 122 ], which determine PB-specific biological effects when applied to cultivated plants.…”
Section: Humic Substances As Microalgae Biostimulantsmentioning
confidence: 99%
“…Several studies have reported on the biostimulant properties of different NPs (Byczyńska, 2017;Juárez-Maldonado et al, 2019;Kumaraswamy et al, 2019). Van et al (2013) (Keswani et al, 2014;Keswani et al, 2016;Bȃrbieru et al, 2019). Venkatachalam et al (2017) studied the plant growth-promoting role of phycomolecules coated ZnO-NPs with phosphorus (P) supplementation in cotton and observed that the combination of bioengineered ZnO-NPs with P supplementation resulted into an increase in biomass, photosynthetic pigments, total soluble proteins, and antioxidant enzyme activities.…”
Section: Biostimulantsmentioning
confidence: 99%